2015
DOI: 10.18632/oncotarget.5613
|View full text |Cite
|
Sign up to set email alerts
|

The oncolytic peptide LTX-315 kills cancer cells through Bax/Bak-regulated mitochondrial membrane permeabilization

Abstract: LTX-315 has been developed as an amphipathic cationic peptide that kills cancer cells. Here, we investigated the putative involvement of mitochondria in the cytotoxic action of LTX-315. Subcellular fractionation of LTX-315-treated cells, followed by mass spectrometric quantification, revealed that the agent was enriched in mitochondria. LTX-315 caused an immediate arrest of mitochondrial respiration without any major uncoupling effect. Accordingly, LTX-315 disrupted the mitochondrial network, dissipated the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…[19][20][21][22][23][24] The chemical modifications of bovine lactoferricin derivatives allowed for the development of a lead compound, LTX-315 with a shorter chemically modified peptide length and optimal (selective) anticancer properties. [25][26][27][28][29] By creating pores and disintegrating the cytoplasmic membranes, as well as targeting the mitochondria, LTX-315 promotes the release of damage-associated molecular patterns (DAMPs) associated with immunogenic cell death (ICD). 26,27,29 Transmission electron microscopy or morphometric analysis of chromatin-stained tumor cells revealed that LTX-315 failed to induce classical 'apoptosis' associated with apoptotic nuclear condensation and caspase-3-dependent cell death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24] The chemical modifications of bovine lactoferricin derivatives allowed for the development of a lead compound, LTX-315 with a shorter chemically modified peptide length and optimal (selective) anticancer properties. [25][26][27][28][29] By creating pores and disintegrating the cytoplasmic membranes, as well as targeting the mitochondria, LTX-315 promotes the release of damage-associated molecular patterns (DAMPs) associated with immunogenic cell death (ICD). 26,27,29 Transmission electron microscopy or morphometric analysis of chromatin-stained tumor cells revealed that LTX-315 failed to induce classical 'apoptosis' associated with apoptotic nuclear condensation and caspase-3-dependent cell death.…”
mentioning
confidence: 99%
“…[25][26][27][28][29] By creating pores and disintegrating the cytoplasmic membranes, as well as targeting the mitochondria, LTX-315 promotes the release of damage-associated molecular patterns (DAMPs) associated with immunogenic cell death (ICD). 26,27,29 Transmission electron microscopy or morphometric analysis of chromatin-stained tumor cells revealed that LTX-315 failed to induce classical 'apoptosis' associated with apoptotic nuclear condensation and caspase-3-dependent cell death. Rather, the oncolytic peptide-mediated cell death exhibited a necrotic phenotype that was not regulated in as much as neither necrostatin-1 nor cyclosporin A compromised cell death.…”
mentioning
confidence: 99%
“…LTX-401 was preferentially enriched in the cytosolic and Golgi fractions, not in mitochondria (Figure 3c). This strongly contrasts with LTX-315 that preferentially enriches in the mitochondrial fraction, 8 not in the Golgi (Figure 3d). Altogether these results suggest that LTX-401 may disrupt the Golgi via a direct effect, upon reaching high local concentrations.…”
Section: Resultsmentioning
confidence: 73%
“…Thus, BFA can reduce the LTX-401-induced signs of mitochondrial membrane permeabilization (such as the release of the intermembrane proteins cytochrome c and SMAC), and DKO of the two pro-apoptotic multidomain proteins BAX and BAK (which both supposedly act on mitochondria) reduces LTX-401-induced killing. Moreover, mitophagy-enforced removal of mitochondria from the cells 8,14 reduces their susceptibility to LTX-401-mediated killing, yet does not reduce LTX-401-induced disruption of the Golgi. This observation again pleads in favor of the interpretation that mitochondria are secondary targets of LTX-401, downstream of its action on the Golgi.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation